2004
DOI: 10.1002/ijc.20276
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis and tumor regression by vesicular stomatitis virus in the presence of gemcitabine in lung cancer

Abstract: Key words: apoptosis; vesicular stomatitis virus; gemcitabine; lung cancer; chemotherapyLung cancer accounts for about 1.5 million cases worldwide and is the leading cause of cancer-related death in both males and females. Non small cell lung cancer (NSCLC) comprises approximately 75-80% of all lung cancers. Despite aggressive approaches made in the therapy of lung cancer in the past decades, the prognosis of NSCLC remains poor, with 5-year survival rates of 5-14%, even if treated with surgery, radiotherapy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…This result not only speaks to the potential of VSV-ΔM51-GFP as an oncolytic agent but also suggests it may also be useful as a sensitizer to chemotherapy. In several cancers, VSV-M51R infection improved doxorubicin treatment by facilitating degradation of the anti-apoptotic protein Mcl-1 (Schache et al, 2009), while another study showed that wt VSV in combination with gemcitabine increased apoptosis and increased killing of lung cancer cell lines in vitro and in vivo (Li et al, 2004). If successful, such combination therapies could allow for equal or greater efficacy at lower doses of chemotherapeutic drug, reducing side effects in patients.…”
Section: Discussionmentioning
confidence: 99%
“…This result not only speaks to the potential of VSV-ΔM51-GFP as an oncolytic agent but also suggests it may also be useful as a sensitizer to chemotherapy. In several cancers, VSV-M51R infection improved doxorubicin treatment by facilitating degradation of the anti-apoptotic protein Mcl-1 (Schache et al, 2009), while another study showed that wt VSV in combination with gemcitabine increased apoptosis and increased killing of lung cancer cell lines in vitro and in vivo (Li et al, 2004). If successful, such combination therapies could allow for equal or greater efficacy at lower doses of chemotherapeutic drug, reducing side effects in patients.…”
Section: Discussionmentioning
confidence: 99%
“…VSV exhibits antitumor activity in syngeneic tumors in immunocompetent mice and human tumor xenografts in nude mice via apoptosis [10][11][12][13][14][15]; however, the risks involved in its use prevent its clinical application. Matrix (M) protein is one of the products of VSV, and it plays a critical role in VSV-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…More than difficult to cure, lung cancer also has a high incidence of recurrence (Khuri et al, 2001;Li et al, 2004;Molina et al, 2006). The non-small cell lung cancer (NSCLC) constitutes a majority of lung cancers.…”
mentioning
confidence: 99%